2023
DOI: 10.1038/s41467-023-40115-1
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-dependent IL-12 signaling in CAR T cells promotes regional to systemic disease targeting

Abstract: Chimeric antigen receptor (CAR) T cell therapeutic responses are hampered by limited T cell trafficking, persistence, and durable anti-tumor activity in solid tumors. However, these challenges can be largely overcome by relatively unconstrained synthetic engineering strategies. Here, we describe CAR T cells targeting tumor-associated glycoprotein-72 (TAG72), utilizing the CD28 transmembrane domain upstream of the 4-1BB co-stimulatory domain as a driver of potent anti-tumor activity and IFNγ secretion. CAR T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…To be noted, we also found that mHAdLyp.sT alone can increase serum levels of GM-CSF and some critical anti-tumor Th1 cytokines such as IL-12 and IFN-γ, and boost the percentage of cytotoxic CD8 + T cells in the spleen and tumor. Especially for IL-12 and IFN-γ, both of which are major determinants of CAR T-cell-based antitumor activity [ 39 , 40 ]. Thus, these results suggest that mHAdLyp.sT may be able to increase the efficacy of adoptively transferred TCR-transduced or CAR-transduced T cells against metastatic cancers as well, by inducing tumor eradication rather than simply slowing the growth.…”
Section: Discussionmentioning
confidence: 99%
“…To be noted, we also found that mHAdLyp.sT alone can increase serum levels of GM-CSF and some critical anti-tumor Th1 cytokines such as IL-12 and IFN-γ, and boost the percentage of cytotoxic CD8 + T cells in the spleen and tumor. Especially for IL-12 and IFN-γ, both of which are major determinants of CAR T-cell-based antitumor activity [ 39 , 40 ]. Thus, these results suggest that mHAdLyp.sT may be able to increase the efficacy of adoptively transferred TCR-transduced or CAR-transduced T cells against metastatic cancers as well, by inducing tumor eradication rather than simply slowing the growth.…”
Section: Discussionmentioning
confidence: 99%
“…The findings illustrated that the incorporation of rhIL-12 alongside anti-CEA CAR T cells notably augmented their capacity to suppress the proliferation of pancreatic tumor cells when compared to solely utilizing CEA CAR T-cell treatment [ 294 ]. Regarding the central role of IL-12 in CAR T cells, a study has proven that membrane-bound IL-12 in CAR T cells targeting TAG72 promotes anti-tumor responses against human ovarian cancer xenograft models [ 295 ]. However, there is a need to apply this approach in PDAC that has not been met.…”
Section: Immunotherapeutic Approaches In Pancreatic Cancer Treatmentmentioning
confidence: 99%
“… 43 Systemic immune responses in non-treated lesions were also observed in several preclinical studies after intratumor T-cell delivery. 44 , 45 , 46 Interestingly, rechallenged cured mice were also able to control both antigen-positive tumor growth and antigen-negative tumors after locoregional adoptive transfer of B7-H3-specific CAR-T cells, 47 suggesting that regional ACT may induce antigen-spreading and long-term systemic immune responses against cancer recurrence.…”
Section: Preclinical Experience Of Intratumoral and Locoregional Adop...mentioning
confidence: 99%
“…The pattern of spread of these types of cancers over a serosa surface may lend them to regional delivery. Intracavitary delivery of engineered TCR-transgenic 53 and CAR-T cells 44 promoted eradication of peritoneal metastases in ovarian tumor mouse models. An enhanced T-cell persistence after intracavitary delivery compared with the i.v.…”
Section: Preclinical Experience Of Intratumoral and Locoregional Adop...mentioning
confidence: 99%